The winning season [videorecording (DVD)] - Strouse, James C. (James Clifton), 1977-; Rockwell, Sam; Roberts, Emma, 1991-; Corddry, Rob; Rios, Emily, 1989-; Mara, Rooney (Lions Gate Home Entertainment, 2010)
Some thematic elements, language including some sexual references, alcohol, abuse, and smoking.